2016
DOI: 10.1103/physrevd.94.044019
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of the rotation and gravity of the Earth in high-energy physics experiments

Abstract: The inertial (due to rotation) and the gravitational fields of the Earth affect the motion of an elementary particle and its spin dynamics. This influence is not negligible and should be taken into account in high-energy physics experiments. Earth's influence is manifest in perturbations in the particle motion, in an additional precession of the spin, and in a change of the constitutive tensor of the Maxwell electrodynamics. Bigger corrections are oscillatory and their contributions average to zero. Other corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 76 publications
(151 reference statements)
1
43
1
Order By: Relevance
“…The vector of the generalized force F α acting on a particle has only a transversal projection, according to (4). As for the spin transport matrix Φ αβ , like any bivector, we can decompose it into a pair of 4-vectors.…”
Section: Projection Methods For Spin In Arbitrary External Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector of the generalized force F α acting on a particle has only a transversal projection, according to (4). As for the spin transport matrix Φ αβ , like any bivector, we can decompose it into a pair of 4-vectors.…”
Section: Projection Methods For Spin In Arbitrary External Fieldsmentioning
confidence: 99%
“…The 0th component of (15) vanishes, which is equivalent to the second condition (4). As a result, the spin evolution equation (15) reduces to the 3-vector form…”
Section: Projection Methods For Spin In Arbitrary External Fieldsmentioning
confidence: 99%
“…Such a situation is of interest, on the one hand, as a fundamental problem of mathematical physics and, on the other hand, it has various important applications ranging form the astrophysical conditions (physical processes near the massive astrophysical objects like neutron stars or black holes) to the highenergy experimental setup on the Earth. In particular, our recent study [42] of the influence of terrestrial gravity and rotation in the precision experiments in storage rings has shown that the corresponding effects are not negligible, and they are manifest in perturbations of particle motion and in additional precession of spin. One should take them into account in the actual and planned g-2 and EDM experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Since the magnetic dipole moment is proportional to the spin [μ = egs/(2mc)], the Hamiltonian of interaction (21) corresponds to the Thomas-Bargmann-Michel-Telegdi equation [31,32] (see also [13,33]) in the general case. This equation describes the spin motion in electromagnetic fields:…”
Section: (2017)mentioning
confidence: 99%
“…Developed methods of the relativistic FW transformation [7][8][9] (see also [10][11][12] and references therein) ensure fulfilling this transformation in arbitrarily strong external fields. While this approach has not been used for strong interactions, it has proven itself as a powerful tool for a description of electromagnetic [11,13,14], gravitational [15][16][17][18][19][20][21], and weak [22,23] interactions of single particles.…”
Section: Introductionmentioning
confidence: 99%